Replacing the Notion of Spacetime Distance by the Notion of Correlation - Kempf, Achim (Frontiers in Physics, 2021)
Spacetime is conventionally viewed as a stage on which actors, in the form of massive and massless matter, move. Here, we explore what may lie beyond this picture. The starting point is the observation that quantum field fluctuations are the more strongly correlated the shorter their spacetime distance. The notion of spacetime distance can, therefore, be replaced by the notion of correlation strength. This suggests a new picture in which abstract 2-point and multi-point correlations are the primary structure, a picture which is essentially information-theoretic. In the low energy regime, the secondary notions of spacetime and of matter would then emerge as approximate representations of the abstract correlators - namely in the form of Feynman rules on curved spacetime.